2023
DOI: 10.1021/acs.jpca.2c07708
|View full text |Cite
|
Sign up to set email alerts
|

Reactions O(3P, 1D) + HCCCN(X1Σ+) (Cyanoacetylene): Crossed-Beam and Theoretical Studies and Implications for the Chemistry of Extraterrestrial Environments

Abstract: Cyanoacetylene (HCCCN), the first member of the cyanopolyyne family (HC n N, where n = 3, 5, 7, ...), is of particular interest in astrochemistry being ubiquitous in space (molecular clouds, solar-type protostars, protoplanetary disks, circumstellar envelopes, and external galaxies) and also relatively abundant. It is also abundant in the upper atmosphere of Titan and comets. Since oxygen is the third most abundant element in space, after hydrogen and helium, the reaction O + HCCCN can be of relevance in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 102 publications
(236 reference statements)
0
19
0
Order By: Relevance
“…For the system involving ethylene, pulsed CMB studies at E c = 6 kcal mol À1 and 3 kcal mol À1 with VUV photoionization detection 93,94 revealed that the contribution of O( 1 D) cannot be neglected and its role was also confirmed in the CMB experiment performed at E c = 35.1 kJ mol À1 by our research group. 90 The second reason is that the system involving atomic oxygen and cyanoacetylene 91 as reference because the two systems, having a comparable entrance potential energy barrier on the triplet PES and having been studied at nearly equal collision energy, have been investigated by using an oxygen beam generated under the same conditions (in the experimental study of the O( 3 P, 1 D) + ethylene reactions the diameter of the nozzle was different) and because the reaction pathway under analysis is the same, i.e., a CO-forming channel (in the experiment involving ethylene, however, the CO-forming channel was not observed to occur 90,93,94 ). Analyzing the TOF spectra, it should be noted that the fingerprint of the CH 2 CNH + CO channel from the reaction of O( 3 P) and O( 1 D) is clearer at Y = 321 than at the angle Y = 441 (that is, very near to the center of mass angle of 451), because at Y CM the relative contribution of the heavy coproduct of the H-displacement channel (1f) is strongly amplified for kinematic reasons (by the CM -LAB transformation Jacobian 60 ), being scattered over a much narrower LAB angular range (see the Newton diagram in Fig.…”
Section: Experimental Results: Lab Product Angular and Tof Distributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the system involving ethylene, pulsed CMB studies at E c = 6 kcal mol À1 and 3 kcal mol À1 with VUV photoionization detection 93,94 revealed that the contribution of O( 1 D) cannot be neglected and its role was also confirmed in the CMB experiment performed at E c = 35.1 kJ mol À1 by our research group. 90 The second reason is that the system involving atomic oxygen and cyanoacetylene 91 as reference because the two systems, having a comparable entrance potential energy barrier on the triplet PES and having been studied at nearly equal collision energy, have been investigated by using an oxygen beam generated under the same conditions (in the experimental study of the O( 3 P, 1 D) + ethylene reactions the diameter of the nozzle was different) and because the reaction pathway under analysis is the same, i.e., a CO-forming channel (in the experiment involving ethylene, however, the CO-forming channel was not observed to occur 90,93,94 ). Analyzing the TOF spectra, it should be noted that the fingerprint of the CH 2 CNH + CO channel from the reaction of O( 3 P) and O( 1 D) is clearer at Y = 321 than at the angle Y = 441 (that is, very near to the center of mass angle of 451), because at Y CM the relative contribution of the heavy coproduct of the H-displacement channel (1f) is strongly amplified for kinematic reasons (by the CM -LAB transformation Jacobian 60 ), being scattered over a much narrower LAB angular range (see the Newton diagram in Fig.…”
Section: Experimental Results: Lab Product Angular and Tof Distributionsmentioning
confidence: 99%
“…of the products is the same of that of the reagents (v r ), the T(y) function is backward-forward symmetric with a maximum at y = 01 and y = 1801. [95][96][97][98][99] Regarding the O( 1 D) + CH 2 CHCN reaction, the T(y) function for the CO-forming channel (2b) was found to be strongly forward biased, as in the case of the O( 1 D) + HCCCN (cyanoacetylene) reaction, 91 indicating an osculating complex mechanism. 97 Regarding the product translational energy distributions, the P E 0 T À Á functions of the two reactive channels of the O( 3 P) + acrylonitrile reaction exhibit a peak well away from zero (at B44 kJ mol À1 for both channels), an indication that the two reactive channels have a sizeable exit potential energy barrier.…”
Section: Experimental Results: Lab Product Angular and Tof Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in the past decades the O( 3 P) + toluene reaction had been extensively studied, the characterization of its detailed mechanism and dynamics, its primary product distribution and role with C2, C3, and C4 unsaturated hydrocarbons, [1][2][3][5][6][7]12,[15][16][17][18][19][20] with benzene, 8,9 pyridine, 11 and the simples unsaturated nitriles. 67,68 It is also a gateway towards the investigation of other O( 3 P) reactions with more complex aromatics, including the prototype of PAHs, naphthalene. 1b).…”
Section: Discussionmentioning
confidence: 99%
“…The electronic partition function of the Cl• atoms was evaluated by considering the splitting of 881 cm –1 between the ground 2 P 3/2 and excited 2 P 1/2 electronic states of Cl• atoms . The CTST method developed by Singleton and Cvetanovic and Alvarez-Idaboy et al , has been successfully employed to a lot of similar reaction systems. …”
Section: Methodsmentioning
confidence: 99%